2010
DOI: 10.1111/j.1462-5822.2010.01516.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma phagocytophilum AptA modulates Erk1/2 signalling

Abstract: SummaryAnaplasma phagocytophilum causes human granulocytic anaplasmosis, one of the most common tick-borne diseases in North America. This unusual obligate intracellular pathogen selectively persists within polymorphonuclear leucocytes. In this study, using the yeast surrogate model we identified an A. phagocytophilum virulence protein, AptA (A. phagocytophilum toxin A), that activates mammalian Erk1/2 mitogenactivated protein kinase. This activation is important for A. phagocytophilum survival within human ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 67 publications
1
51
0
Order By: Relevance
“…We detected expression of 27 hypothetical proteins in tick salivary glands by proteomics or RNA-seq (Table 3 and Table 4). Some of these proteins have previously been characterized in HL-60 cultures for their roles in A. phagocytophilum infection (14,15,34) or identified as immunoreactive proteins (24). Two hypothetical proteins, APH_0220 and APH_0792, were classified as among the most abundant in the HL-60 culture proteome (23).…”
Section: Resultsmentioning
confidence: 99%
“…We detected expression of 27 hypothetical proteins in tick salivary glands by proteomics or RNA-seq (Table 3 and Table 4). Some of these proteins have previously been characterized in HL-60 cultures for their roles in A. phagocytophilum infection (14,15,34) or identified as immunoreactive proteins (24). Two hypothetical proteins, APH_0220 and APH_0792, were classified as among the most abundant in the HL-60 culture proteome (23).…”
Section: Resultsmentioning
confidence: 99%
“…The ectopic expression of the A. phagocytophilum AptA protein activates ERK1/2 in HL-60 cells (Fig. 4) (210). AptA interacts with the intermediate filament protein vimentin, which is essential for A. phagocytophilum-induced ERK1/2 activation and infection (210).…”
Section: Other Host Cell Signals Activated and Required Formentioning
confidence: 99%
“…(132). Several hypothetical proteins in A. phagocytophilum were found to be surface-exposed proteins, inclusion membrane proteins, and T4S substrates that confer unique phenotypes to this bacterium (74,99,100,166,195,210). A. phagocytophilum and Rickettsia prowazekii share 469 genes (61), and both bacteria cannot use glucose as a carbon or energy source.…”
Section: Genomic Featuresmentioning
confidence: 99%
“…Rifampicin and the new fluoroquinolone antibiotic trovafloxacin are effective in vitro (Horowitz et al, 2001;Klein et al, 1997), but limited in vivo studies are available to confirm the in vitro data (Buitrago et al, 1998;Krause et al, 2003) A. phagocytophilum resides and proliferates in the professional killer cells of the host and disrupts many cell functions, in particular by modulating host-cell signalling to benefit itself and establish infection in the host (Rikihisa, 2003(Rikihisa, , 2006. It has been shown that A. phagocytophilum activates extracellular signal-regulated kinase (ERK) in neutrophils and HL-60 cells (Lee et al, 2008;Sukumaran et al, 2011;Xiong et al, 2009) and that ERK activation is required for A. phagocytophilum infection (Xiong et al, 2009). One of the best-characterized ERK activation pathways is Ras/Raf/MEK/ ERK (Roux & Blenis, 2004), and manumycin A, a farnesyltransferase inhibitor, is known to inhibit this pathway by inhibiting Ras farnesylation (Ito et al, 1996).…”
Section: Introductionmentioning
confidence: 66%
“…Therefore, A. phagocytophilum infection may activate ERK in an alternative pathway. Recently, an A. phagocytophilum virulence protein, AptA, was identified as being involved in the activation of ERK1/2 during A. phagocytophilum infection (Sukumaran et al, 2011).…”
Section: Discussionmentioning
confidence: 99%